2018
DOI: 10.3892/ol.2018.8966
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring immunoglobulin heavy chain and T‑cell receptor gene rearrangement in cfDNA as minimal residual disease detection for patients with acute myeloid leukemia

Abstract: The present study aimed to examine whether monoclonal immunoglobulin heavy chain (IGH) or T-cell receptor (TCR) gene rearrangement in cell-free DNA (cfDNA) may be used for minimal residual disease (MRD) monitoring in patients with acute myeloid leukemia (AML). Monoclonal IGH and TCR rearrangement in cfDNA were monitored in patients with AML. A total of 94 (40%) patients had monoclonal IGH or TCR rearrangements in cfDNA at diagnosis; 84% of these patients (79 cases) achieved complete remission following 1–3 cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 25 publications
2
11
0
Order By: Relevance
“…High expression of EMTrelated gene vimentin is signi cantly associated with poor prognosis of AML [52]. Zhong et al showed that TCR gene rearrangement can be used to monitor minimal residual disease in AML patients [53]. Previous studies showed that WT1-speci c T cell receptor can be used for the treatment of AML, and can prevent the recurrence of AML after hematopoietic cell transplantation [54,55].…”
Section: Discussionmentioning
confidence: 99%
“…High expression of EMTrelated gene vimentin is signi cantly associated with poor prognosis of AML [52]. Zhong et al showed that TCR gene rearrangement can be used to monitor minimal residual disease in AML patients [53]. Previous studies showed that WT1-speci c T cell receptor can be used for the treatment of AML, and can prevent the recurrence of AML after hematopoietic cell transplantation [54,55].…”
Section: Discussionmentioning
confidence: 99%
“…A resent research suggests that patients with autosomal recessive agammaglobulinemic have IGHM gene mutations [17]. Also, the mu-chain of immunoglobulin gene rearrangement was detected in myeloid leukemia cells from AML patients, and the survival rate of AML patients was signi cantly lower [13,14,16,18,19]. Neeraj et al also found that gene rearrangement of IGHM in the diffuse large B cell lymphoma (DLBCL) [20].…”
Section: Discussionmentioning
confidence: 99%
“…In 2020, Nicholas et al performed targeted NGS of ctDNA and BM DNA in patients with AML and suggested that they may be complementary to the assessment and monitoring of patients [ 88 ]. Zhong et al detected monoclonal immunoglobulin gene rearrangement in AML ctDNA, which is expected to be applied in MRD monitoring [ 89 ]. The detection of IgH and TCR rearrangement is common in lymphoid malignancy but rare in AML.…”
Section: Utility Of Ctdna Characterization In Hematopoietic Tumorsmentioning
confidence: 99%